Genome-wide identification and functional analysis of the GRAS gene family in Medicago lupulina L - Li Fan; Ruimiao Wang; Pedro García-Caparrós; Lihua Meng; Xudong Sun (BMC Genomics)
Abstract Background Transcription factors encoded by GRAS genes play pivotal roles in a wide range of biological processes, including signal transduction, plant growth and development, and responses to various abiotic and biotic stresses. Nevertheless, to date, the GRAS gene family has not been previously identified or analyzed in Medicago lupulina L. Results In this study, bioinformatic approaches were used to analyze genomic data of M. lupulina obtained from our laboratory, resulting in the identification of 52 GRAS genes (designated as MlGRASs). We predicted and analyzed the physicochemical properties, subcellular localization, protein structures, phylogenetic relationships, gene structures, and sequence characteristics of these genes. Phylogenetic analysis showed that 52 MlGRASs were categorized into eight different subfamilies: LILIUM LONGIFLORUM SCR-LIKE (LISCL), SHORT ROOT (SHR), PHYTOCHROME A SIGNAL TRANSDUCTION 1 (PAT1), SCARECROW-LIKE 3 (SCL3), DELLA, HAIRY MERISTEM (HAM), LATERAL SUPPRESSOR (LS) and SCARECROW (SCR). Notably, we identified 10 M. lupulina GRAS genes belonging to the PAT1 subfamily. Experimental results from RT-qPCR analysis demonstrated that MlPAT1s genes were expressed in leaves, stems and roots of M. lupulina. Moreover, in the graft union, the expression levels of most MlPAT1s were higher than those in the wild type M. lupulina. To further predict the potential functions of MlPAT1s genes, we performed molecular cloning and transcriptional activation assays on MlGRAS3/31/35/62/65. The transcriptional activation assay revealed that 35 S:GFP-MlGRAS31/35/62/65 positively regulated the expression of MlDOF3.4, a gene implicated in cell proliferation and regeneration. Conclusions This study provided a theoretical framework for further investigation into the roles of PAT1 proteins in M. lupulina.